The effect of monopoly regulation on the timing of investment - Jörg Borrmann; Gert Brunekreeft (Jacobs University Bremen, Bremer Energie Institut, 2011)
This paper contributes a theoretical analysis of the effects of different types of regulation on the timing of monopoly investment in a setting with lumpy investment outlays. Concentrating on the case where investment increases the regulatory asset base, we distinguish between price-based regulation and cost-based regulation. Under cost-based regulation, investment triggers a change of regulated prices, whereas, under price-based regulation, investment does not affect them. To motivate investment, we focus on wear and tear leading to replacement investment and on demand growth resulting in expansion investment. Our main conclusion is that cost-based regulation accelerates investment compared to price-based regulation.
Keywords: D42; G00; L51; 330; Cost-based regulation; Expansion investment; Investment timing; Monopoly; Price-based regulation; Replacement investment